2016
DOI: 10.1007/s12403-016-0226-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Arsenic and Uranium Concentrations in Unregulated Water Sources on the Navajo Nation, USA

Abstract: Regional water pollution and use of unregulated water sources can be an important mixed metals exposure pathway for rural populations located in areas with limited water infrastructure and an extensive mining history. Using censored data analysis and mapping techniques we analyzed the joint geospatial distribution of arsenic and uranium in unregulated water sources throughout the Navajo Nation, where over 500 abandoned uranium mine sites are located in the rural southwestern United States. Results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 30 publications
3
107
0
Order By: Relevance
“…To evaluate metal exposure via drinking water, DiNEH staff collected water samples for 124 water sources (101 unregulated, 23 regulated) from 2003 to 2010 following US Environmental Protection Agency analysis methods as described in Hoover et al . 3 A small subset of samples was analyzed at the Carlsbad Environmental Monitoring and Research Center or at Stanford University. Navajo Nation EPA provided public water quality data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate metal exposure via drinking water, DiNEH staff collected water samples for 124 water sources (101 unregulated, 23 regulated) from 2003 to 2010 following US Environmental Protection Agency analysis methods as described in Hoover et al . 3 A small subset of samples was analyzed at the Carlsbad Environmental Monitoring and Research Center or at Stanford University. Navajo Nation EPA provided public water quality data.…”
Section: Methodsmentioning
confidence: 99%
“…1 Today, there are more than 500 abandoned uranium mines (AUM) and 4 abandoned mill sites that continue to pose a risk to these communities. 2 Uranium, arsenic (As), nickel (Ni), vanadium (V) and copper (Cu) are among the major contaminants still found in the soil, air and ground water 3 to which this population may be chronically exposed. 4 The impact of such exposures on cardiovascular health remains poorly researched.…”
Section: Introductionmentioning
confidence: 99%
“…In oxic environments, U exists predominately in the 16 oxidation state as the uranyl oxycation (UO 21 2 ) and has high chemical toxicity (Markich, 2002). The US Environmental Protection Agency's maximum contaminant limit for U in drinking water is 30 lg L 21 ($0.13 lM), however, groundwater concentrations in the US frequently exceed this limit (Focazio et al, 2006;Hoover et al, 2016). Studies of the U response in anaerobic and aerobic bacteria have revealed a plethora of different stress responses that range from DNA damage, oxidative stress, protein misfolding, to cell envelope stress (Bencheikh-Latmani et al, 2005;Junier et al, 2011;Khemiri et al, 2014, Li et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Sampling methods were conducted in a prospective fashion including one-time grab samples and repeat sample collection to observe seasonal variability. Chemical concentrations were measured using Inductively Coupled Plasma (ICP) – Optical Emissions Spectroscopy [15, 16, 1921], ICP – Atomic Emissions Spectroscopy [15, 16, 19, 20], ICP – Mass Spectroscopy [13, 1517, 1924], or Graphite Furnace Atomic Absorption Spectroscopy [18]. Additionally, concentrations of As, U, chromium (Cr), lead (Pb), iron (Fe), and vanadium (V) were measured in mine waste, soil, sediment and other solid material using x-ray fluorescence [21, 22], X-ray diffraction, scanning electron microscopy, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy [21].…”
Section: Resultsmentioning
confidence: 99%
“…In the FRONTIER study in west TX, direct measurements were used in geospatial models to estimate groundwater concentrations at unsampled locations [13, 14]. Hoover et al (2017), used geospatial spatial analysis methods to assess the influence of distance from an abandoned U mining (AUM) site on levels of As and U measured in UWSs on the Navajo Nation [19]. Additionally, Hoover et al (2018) identified metal mixtures found in UWSs on the Navajo Nation and evaluated the geographic distribution of these metal mixture clusters using spatial analysis methods [20].…”
Section: Discussionmentioning
confidence: 99%